2015
DOI: 10.4236/abb.2015.61005
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Principle Revisited: Theory of Protein Folding

Abstract: Anfinsen's thermodynamic hypothesis is reviewed and misunderstandings are clarified. It really should be called the thermodynamic principle of protein folding. Energy landscape is really just the mathematical graph of the Gibbs free energy function () X; , N G U E , a very high dimensional hyper surface. Without knowing it any picture of the Gibbs free energy landscape has no theoretical base, including the funnel shape claims. New insight given by newly obtained analytic Gibbs free energy function () X; , N G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…That law is the Thermodynamic Principle of Protein Folding [1], it is just the Second Law of Thermodynamics since Anfinsen and others already shown that the folding process is spontaneous. In the protein folding case, the second law is that the Gibbs free Via quantum statistics applied to a tiny thermodynamic system X S which is tailor made for the conformation X and its immediate physiological environment U E , we have derived the conformational Gibbs free energy (CGFE) function ( ; , ) G X U E U for globular proteins U 4].…”
Section: Introduction: a Single Molecule View Of Protein Foldingmentioning
confidence: 99%
“…That law is the Thermodynamic Principle of Protein Folding [1], it is just the Second Law of Thermodynamics since Anfinsen and others already shown that the folding process is spontaneous. In the protein folding case, the second law is that the Gibbs free Via quantum statistics applied to a tiny thermodynamic system X S which is tailor made for the conformation X and its immediate physiological environment U E , we have derived the conformational Gibbs free energy (CGFE) function ( ; , ) G X U E U for globular proteins U 4].…”
Section: Introduction: a Single Molecule View Of Protein Foldingmentioning
confidence: 99%